Lifestyle and Immunity Boosting Practices During COVID-19 Pandemic Among the Population of Rajshahi District, Bangladesh (Journal of Bio-Science, 2023)
Coronavirus disease 2019 (COVID-19) pandemic represents a massive impact on human health, causing sudden lifestyle changes, through social distancing and isolation at home, with social and economic consequences. The aim of the study was to determine both of community and gender-based distribution of perception, attitude, preventive measures, changing lifestyle regarding COVID-19 and to help the Government and policymakers to take indispensable steps. This cross-sectional survey self-administered online-based study was carried out after the declaration of strict initial lockdown enforced in Bangladesh. The study was conducted in Rajshahi district from 30 March 2020 to 31 August 2020, a very critical time of mental suffering and lockdown. A total of 651 respondents from Rajshahi district in Bangladesh participated in the survey, and by a self-administered questionnaire, designed in the language of English. Among the collected responses, 535 were considered for the analysis, which largely belonged to Rajshahi’s middle to upper socio-economic status (SES). The data analysis was performed using Microsoft Excel 2019 and SPSS version 25.0 (Chicago, IL, USA). The data were analyzed by using descriptive statistic, chi-square test and z-proportional test. In this empirical study, 278 males and 257 females participated. More than one-tenth of males and 35% of females were not conscious of the type of Coronavirus. A lot of misperception about the incubation period of COVID-19 existed among participants. The research observed that 34.2%, of males and 25.3% of the female study population had no opinion about the treatment of COVID-19 and 27.3% of males and 21.8% of females gave a verdict that COVID-19 had no available treatment. The study discovered more surprisingly that females (67.3%), greater than males (65.5%) did not want to stay at home during the lockdown. Positively 87.8% of males and 70.4% of females washed their hands with soap or used sanitizer after coming back from outside. The consumption of a balanced diet increased by males and females was 13.3% and 6.7% respectively. Z-proportional test showed that regarding COVID-19, there were significant difference between male and female’s conception and precaution (p